INVESTIGATING THE RELATIONSHIP BETWEEN SURGICAL TEAM COMMUNICATION AND PATIENT OUTCOMES - AI, SZ; HUSSAIN, S; ALAM, SI; HUSSAIN, Y; ASHRAF , M; ALI , N (Biological and Clinical Sciences Research Journal, 2024)
Surgical team plays a vital role in the care of patients during the surgery. For safe patient outcomes, surgical team members must effectively communicate within the surgical site. Communication breakdowns in the complex operating room atmosphere can result in unfavorable outcomes. To reduce risks, avoid errors and provide the best possible care for patients, the surgical team must communicate clearly and effectively with one another. Enhancing the quality of surgical treatment requires an understanding of the connection between communication and patient results. Objective: The purpose of this study was to investigate the connection between patient satisfaction outcomes and surgical communication between teams focusing on how the improved communication practices can enhance the patient safety in terms of care quality and satisfaction level in surgical setting. Method: The study comprised of 187 health care providers between the ages of 18 and 65 who were examined for the association between surgical team communication and patient outcomes after ethical approval from Hospital ethical committee. Descriptive cross-sectional study was carried out in the District Headquarters Teaching Hospital, Kohat Development Authority Kohat from January 2022 to July 2022. Data was Analyzed on SPSS and shown in tables. Results: The analysis shows a strong positive correlation (.595) between team communication and patient outcomes, with healthcare professionals that rates the quality of communication at an average of 3.84 out of 5, which is closely linked to a decrease in surgical complications and an increase in patient satisfaction. Sticking and communicating according to communication protocols was rated at 3.76, underlining its importance in patient safety improvements. Conclusions: The study affirms the crucial impact of effective communication among surgical team members on improving patient outcomes and safety in the operating site. The enhanced communication directly relates with faster patient recovery, lesser complications and higher patient satisfaction.